Recent trends in user studies: action research and qualitative methods - T.D. Wilson (Information Research: An International Electronic Journal)
This paper was commissioned by Professor Gernot Wersig of the Freie Universität, Berlin in 1980, as part of his Project, Methodeninstrumentarium zur Benutzforschung in Information und Dokumentation. It attempted to set out what was, for the time, a novel perspective on appropriate methodologies for the study of human information seeking behaviour, focusing on qualitative methods and action research, arguing that the application of information research depended up its adoption into the managerial processes of organizations, rather than its self-evident relationship to any body of theory.